HEK293T Cells Are Heterozygous for CCR5 Delta 32 Mutation. - Chunxia Qi (PLoS ONE, 2016)
C-C chemokine receptor 5 (CCR5) is a receptor for chemokines and a co-receptor for HIV-1 entry into the target CD4+ cells. CCR5 delta 32 deletion is a loss-of-function mutation, resistant to HIV-1 infection. We tried to induce the CCR5 delta 32 mutation harnessing the genome editing technique, CRISPR-Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats, CRISPR and CRISPR associated protein 9, Cas9) in the commonly used cell line human embryonic kidney HEK 293T cells. Surprisingly, we found that HEK293T cells are heterozygous for CCR5 delta 32 mutation, in contrast to the wild type CCR5 cells, human acute T cell leukemia cell line Jurkat and human breast adenocarcinoma cell line MDA-MB-231 cells. This finding indicates that at least one human cell line is heterozygous for the CCR5 delta 32 mutation. We also found that in PCR amplification, wild type CCR5 DNA and mutant delta 32 DNA can form mismatched heteroduplex and move slowly in gel electrophoresis.